CFD study of fouling phenomena in small-scale biomass boilers: Experimental validation with two different boilers. (September 2019) - Chapela, S.; Porteiro, J.; Garabatos, M.; Patiño, D.; Gómez, M.A.; Míguez, J.L.
Abstract: The use of biomass is growing as it is considered as a renewable energy by a society with increasing ecological awareness. Biomass has the advantage of being easily used in existing installations with non-renewable solid fuels, either as a final fuel or as a transition fuel. However, biomass use presents serious operational problems, such as slagging and fouling, which have slowed its development. This work continues the development of an advanced and flexible fouling model that is embedded in a fixed-bed biomass combustion model developed by the University of Vigo for the commercial code, ANSYS-Fluent. The modifications to the algorithm enable the analysis of commercial water-tube and fire-tube combustion systems, with diverse types of fuel-feeding systems. To validate the model, a numerical study of the combustion and fouling phenomena of two commercial systems that have already been analysed experimentally and published was carried out. The results obtained are in good agreement with the experimental results and demonstrate the accuracy and flexibility of the proposed model. After this validation, future research lines can be opened that consider more complex phenomena. Highlights: Modification of fouling algorithm to work properly on commercial systems. Study on fire-tube and water-tube boilers. Adaptation to non-continuous fuel feeding systems. Experimental validation of the numerical results with reasonable accuracy. Estimation of the profile of the fouling layer.